Integrated PRRSV prevention and control strategy based on the One Health concept: across the boundaries of virology, ecology and public health - Chen, Hongbo; Weng, Chengzhen; Huang, Xinxin; Li, Xiaobing; Duan, Dianning (Frontiers in Microbiology, 2025)
Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) poses a major threat to global swine production, with substantial economic losses and serious animal welfare concerns. Although PRRSV is not considered a zoonotic agent, its control exemplifies the necessity of a One Health approach, incorporating virological, ecological, immunological, and agricultural dimensions. This article contends that the impact of PRRSV extends beyond porcine populations, significantly contributing to the emergence of antimicrobial resistance (AMR) via secondary bacterial infections and the consequent misuse of antibiotics. Moreover, the environmental persistence of the virus and its potential for indirect transmission raise critical ecological questions that remain unresolved. By synthesizing current evidence, this review delineates the complex interrelationships among PRRSV outbreaks, patterns of antimicrobial use, and environmental contamination. This study propose an integrated One Health framework for PRRSV surveillance and control, emphasizing the implementation of genomic tools, systematic environmental monitoring, and enhanced collaboration among public health, veterinary, and environmental sectors. Integrating these disciplines is crucial to alleviating the multidimensional challenges posed by PRRSV, thereby protecting animal welfare, supporting sustainable agriculture, and strengthening global public health.